KEWENANGAN KOMISI YUDISIAL DALAM PERSPEKTIF POLITIK HUKUM PERADILAN , ETIKA DAN MORAL - Handoyo, Budi (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
The amendment of the 1945 Constitution has created a new policy direction towards the political changes of national law. One such policy is the creation of two new judicial institutions, namely the Constitutional Court and the Judicial Commission. The background of the formation of a judicial commission is as a watchdog of judges, so that the independence possessed by judges is not misused. The constitutional basis of the Judicial Commission is set forth in Article 24B paragraph (1) of the 1945 Constitution. It states that the Judicial Commission is independent in its capacity to propose the appointment of Supreme Court justices and to have other powers in order to safeguard and uphold the honor, dignity, and behavior of judges. Regarding the authority of the duties and functions of the Judicial Commission is further stipulated in Law No. 18 of 2011 on Amendment to Law Number 22 Year 2004 concerning the Judicial Commission. The principal authority of the Judicial Commission legislation, as a means of controlling the conduct and conduct of judges, and as a means or tool to change the behavior of judges in a better and ethical and moral direction. The provisions in the new Judicial Commission Law have reinforced and expanded sanctions in the event of alleged violations of the Code of Ethics and judge behavior which include mild sanctions, moderate sanctions and severe sanctions.